The development and maintenance of immunity against visceral leishmaniasis - Tiwari, Rahul; Kumar, Awnish; Singh, Vishal Kumar; Rajneesh,; Chauhan, Shashi Bhushan; Sundar, Shyam; Nylén, Susanne; Engwerda, Christian; Kumar, Rajiv (Frontiers in Immunology, 2024)
Understanding the development and maintenance of immunological memory is important for efforts to eliminate parasitic diseases like leishmaniasis. Leishmaniasis encompasses a range of pathologies, resulting from infection with protozoan parasites belonging to the subgenera Leishmania and Viannia of the genus Leishmania. A striking feature of these infections is that natural or drug-mediated cure of infection generally confers life-long protection against disease. The generation of protective T cell responses are necessary to control Leishmania infections. CD4+ T helper (Th) cells orchestrate immune responses in leishmaniasis and IFNγ+ Tbet+ CD4+ T (Th1) cells are required for the activation of phagocytes to kill captured or resident parasites, while other Th cell subset, including FoxP3+ natural regulatory T cells and Th2 cells can promote disease progression by suppressing the activities of Th1 cells. Upon resolution of a primary Leishmania infection, different subsets of CD4+ T cells, including tissue-resident memory T cells, effector memory T cells, central memory T cells, and short-lived effector T cells, help to confer resistance against reinfection. To maintain long-term protective Leishmania-specific CD4+ T cells responses, it is believed that persistent parasites or re-exposure to parasites at regular intervals is required (concomitant immunity). Despite the advances in our understanding about the immune responses during leishmaniasis, the generation of long-lasting protective immunity via vaccination has yet to be achieved. In this review, we summarize our current understanding about the formation and maintenance of immunological memory and control of leishmaniasis at the individual and population level. We will focus on Indian visceral leishmaniasis and discuss T cell responses that contribute to susceptibility to leishmaniasis, parasite persistence in populations and the environment, as well as describing advances in the development of leishmaniasis vaccines aimed at inducing protective CD4+ T cell responses.